2017
DOI: 10.1186/s13012-017-0696-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research and integrated knowledge translation: advancing the co-creation of knowledge

Abstract: BackgroundBetter use of research evidence (one form of “knowledge”) in health systems requires partnerships between researchers and those who contend with the real-world needs and constraints of health systems. Community-based participatory research (CBPR) and integrated knowledge translation (IKT) are research approaches that emphasize the importance of creating partnerships between researchers and the people for whom the research is ultimately meant to be of use (“knowledge users”). There exist poor understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
386
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(396 citation statements)
references
References 52 publications
(55 reference statements)
2
386
0
8
Order By: Relevance
“…Other partnership studies have also concluded that there are no dominant theories to guide partnership initiation [46,47], as was found in this review. Another review, that examined the histories and traditions of community-based participatory research and IKT, also found that co-creation of knowledge is referred to with different labels [16]. In addition, similar to other studies, our review failed to identify outcomes definitively associated with partnership initiation processes, enablers or barriers, although several hypothetical outcomes were proposed [9].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other partnership studies have also concluded that there are no dominant theories to guide partnership initiation [46,47], as was found in this review. Another review, that examined the histories and traditions of community-based participatory research and IKT, also found that co-creation of knowledge is referred to with different labels [16]. In addition, similar to other studies, our review failed to identify outcomes definitively associated with partnership initiation processes, enablers or barriers, although several hypothetical outcomes were proposed [9].…”
Section: Discussionmentioning
confidence: 59%
“…In other words, the benefits of researcher and research user partnerships may not be realised if flourishing partnerships are not established at the outset. While previous reviews [9] and concept analyses [10,11,16,17] of researcher and research user partnerships have been published, none of those specifically assessed partnership initiation in depth. Bush et al [17] concluded that co-creation partnerships, that is, partnerships to co-create knowledge, initiated by research user organisations appear to have greater beneficial outcomes than consultative type partnerships initiated by either universities or research user organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Some observations regarding the use of participatory methods to improve and evaluate integrated care practice can also be made based on this case study. In line with the EIT and other models (Glasgow et al, ; Horowitz, Robinson, & Seifer, ; Jull, Giles, & Graham, ), the needs and priorities of local stakeholders were the starting point of the improvement process. This approach facilitated the establishment of partnerships between researchers and stakeholders, but also between stakeholders themselves, and it stimulated stakeholders to challenge their established mind‐set and views (Eyre et al, ; Martin Fortin & Moira, ).…”
Section: Discussionmentioning
confidence: 92%
“…The results of the present study contribute to personcentred health care design by creating partnerships between researchers and the people for whom the research is ultimately meant to be of use. 34 This challenges assumptions of experts and values the consideration of LTR life priorities during the course of recovery.…”
Section: Key Insightsmentioning
confidence: 99%